URGENSI REVITALISASI PANTAI PASIR PANJANG SEBAGAI ASET PARIWISATA OLEH PEMERINTAH KOTA SINGKAWANG - NIM. A1011211008, GALUH DAMAYANTI (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract Revitalization is an urgent step not only regarding physical improvements, but also touches on policy, governance, and justice aspects in the use of the budget obtained from the levy. In addition, with the revitalization of Pasir Panjang Beach, the level of visitor satisfaction has increased, which in turn can increase the number of visitors. Thus, regional revenue from the business actors' tax sector and levies can increase. Revitalization can also have an impact on the return of economic enthusiasm in the tourist attraction area. Traders and business actors who rely on the crowds in Pasir Panjang, can certainly feel an increase in sales, along with the increasing number of visitors. Therefore, the author is interested in conducting a research entitled